Mid- to Long-Term Outcomes in Management of Spontaneous Isolated Coeliac Artery Dissection (SICAD). (February 2020) - Kang, So Hyun; Park, Hyung Sub; Yoon, Chang Jin; Shin, Chang Sik; Yoo, Kwon Cheol; Lee, Taeseung
Abstract : Objective: Spontaneous Isolated Coeliac Artery Dissection (SICAD) is a rare disease with few reports of management strategies. This study reports the mid- to long-term outcomes of conservative management and endovascular intervention of SICAD treatment. Methods: Sixteen patients presenting with symptomatic SICAD from September 2006 to October 2018 were reviewed retrospectively. The clinical manifestations, initial radiological findings, methods of treatment, and serial follow up studies were analysed. Results: The mean age of the patients was 51.2 ± 7.9 years, with a median follow up of 33.3 (range 1.0–118.9) months. Four patients received early intervention because of aneurysmal dilatation or distal hypoperfusion. Four patients who received conservative management showed progression of disease and were recommended for delayed intervention. Although collaterals prevented further hepatic ischaemia, one of these four patients failed in delayed intervention because of extensive thrombi completely occluding the hepatic artery. In the remaining eight patients who were managed conservatively, three (37.5%) showed regression of disease, one (12.5%) showed partial regression, and five (62.5%) showed no change in intimal flap or thrombosis, but all had symptomatic improvement. The median follow up duration for the seven patients who underwent successful intervention was 77.3 (range 34.3–118.9) months, and all stenting remained patent during the follow up period. Conclusion: Early intervention in symptomatic SICAD patients may be necessary in over 50% of patients, and endovascular stenting has durable long term outcomes.